Quantum Chaos in Time Series of Single Photons as a Superposition of Wave and Particle States - Benjamín David Mendoza; Diego Alberto Lara; Jehú López-Aparicio; Gustavo Armendáriz; Leonardo López-Hernández; Víctor Velázquez; Edna Magdalena Hernández; Marcela Grether; Enrique López-Moreno; Alejandro Frank (Photonics, 2021)
We build a time series of single photons with quantum chaos statistics, using a version of the Grangier anti-correlation experiment. The criteria utilized to determine the presence of quantum chaos is the frame of the Fano factor and the power spectrum. We also show that photons with chaotic statistics are in a balanced superposition of photons with both wave-like and particle like behaviors. To support the presence of quantum chaos, we study both Shannon’s entropy, and the complexity of single photons time series.